Paleoartistic study on the Tyrannosaurus Rex in the audiovisual industry (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
Tyrannosaurus Rex, as known as ‘T-Rex’, is one of the most recognizable and represented dinosaurs in diverse media. Every design that adheres with paleontological data has a paleoartistic background; this article shows research about the development of the creature within different production companies of the audiovisual industry in order to analyze the reconstruction of tyrannosaurus within the paleoart conceptual framework, so we could infer trends and future projection of its image.
Keywords: Paleoart; Scientific drawing; Comparative Anatomy